2021
DOI: 10.3390/ijms22094693
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modifications Associated with Exposure to Endocrine Disrupting Chemicals in Patients with Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) remains a significant clinical and public health issue due to its increasing prevalence and the possibility for numerous short- and long-term complications. The growing incidence of GDM seems to coincide with the widespread use of endocrine disrupting chemicals (EDCs). The extensive production and common use of these substances in everyday life has resulted in constant exposure to harmful substances from the environment. That may result in epigenetic changes, which may manif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 137 publications
0
8
0
Order By: Relevance
“…diet, obesity, smoking, hormone supplementation) [ 14 , 29 , 30 ] and the environment (e.g. exposure to endocrine disruptors) [ 31 ] to which the patient has been or is exposed. To the extent that the lifestyle could be inferred from the epigenetic state, a change in the principle of autonomy can occur.…”
Section: Ethical Implications Of Epigenetic-predictive Biomarkersmentioning
confidence: 99%
“…diet, obesity, smoking, hormone supplementation) [ 14 , 29 , 30 ] and the environment (e.g. exposure to endocrine disruptors) [ 31 ] to which the patient has been or is exposed. To the extent that the lifestyle could be inferred from the epigenetic state, a change in the principle of autonomy can occur.…”
Section: Ethical Implications Of Epigenetic-predictive Biomarkersmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) is a type of diabetes that is first diagnosed during pregnancy, with increasing incidence in recent decades. GDM is associated with increased risks of serious adverse pregnancy outcomes and birth outcomes, including preeclampsia and spontaneous abortion, maternal metabolic syndrome, fetal anomalies, neonatal hypoglycemia, and newborn asphyxia . Epidemiologic evidence has demonstrated that exposure to heavy metals, industrial organic pollutants, and pesticides is an environmental risk factor for GDM. Although urinary 3-PBA has been frequently detected in pregnant populations from different regions, whether exposure to pyrethroids contributes to the development of GDM remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic regulation has a crucial potential in the pathogenesis of GDM. 8 The epigenetic regulation contains histone modification, DNA methylation along with microRNA (miRNA) depletion, which are strongly associated with each other and affect protein synthesis patterns. 9 MiRNAs belong to highly conserved small noncoding RNAs and affect the progression of diseases via post-transcriptionally modulating gene expression.…”
Section: Introductionmentioning
confidence: 99%